Razredi delnic in prednostne delnice - Kocbek, Marijan (Podjetje in delo, 2015)
The article addresses some o/ the controversial issues relating to the characteristics of preference shares. In line with the German Companies Act -AktG, the Slovenian counterpart ZGD-1 does not allow preferential management rights (e.g. multiple voting rights), permitting only advantages in terms of property rights. Since the law only generally sets out the rights, stemming from preference shares, they need to be precisely regulated in the articles of association of the company. The author discusses the manner in which non-voting shares can be specified in the articles of association of the company in accordance with the case-law. In particular, the author deals with the possibilities of determining the amount of dividend from cumulative participating shares in the articles of association of the company. Contrary to a Slovenian Supreme Court decision, the author is of the opinion that this matter is subject to an autonomous regulation. To clarify this issue indisputably the author alternatively proposes an appropriate change to the provisions of the forthcoming amendment ZGD-1 I.
Keywords: delnice; delničarji; delniške družbe; dividende; pravice